Complicated abdominal wall hernia mimicking an abdominal wall abscess: A case report - Sanae, Amalik (Radiol Case Rep, 2021)
Abdominal wall hernias are a common imaging finding. Their most common complications include bowel obstruction, incarceration, strangulation and trauma. We report an exceptional case of spigelian hernia in 55 years old women complicated by perforation and massive subcutaneous emphysema which was correctly diagnosed by CT scan. This case showed the interest of CT scan with multiplanar reconstructions in the confirmation of the diagnosis.